ISOTOPE AGE OF SUBVOLCANIC GRANITOID ROCKS OF THE EARLY PROTEROZOIC PANARECHKA VOLCANOTECTONIC STRUCTURE, KOLA PENINSULA - Skuf'in P.K.; Bayanova T.B.; Mitrofanov F.P. (My University, 2006)
The Panarechka volcanotectonic calderalike structure (PVTS) was found in the Early Proterozoic Pechenga–Varzuga Rift Belt (fault-lineament) of the Kola region. This is an oval body (21 × 8 km in size) that extends in a NW direction and is discordant with host rocks of the Il’mozero Formation and Tominga Group of the Imandra–Varzuga structural zone. The volcanic structure is filled with arkosic and graywacke sandstones and basaltic lavas of the Panarechka Formation ~1000 km thick.
Keywords: Panarechka; Kola peninsula; Proterozoic; Precambrian::Proterozoic; Докембрий::Протерозой